Integrated Marketing Communication in the Social Media Era: Performativity, Identity, and User-Generated Content in Indonesia's Digital Consumer Culture - Hilarius Bambang Winarko; Endah Fantini (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Indonesian brands increasingly rely on story-driven Integrated Marketing Communication (IMC), yet the role of User-Generated Content (UGC) in shaping consumer identity on social media remains underexplored. Objective: This study examines the intersection of Integrated Marketing Communication (IMC) practices and consumer identity construction on social media, focusing on User-Generated Content (UGC), such as unboxing videos, haul videos, and brand challenges, within Indonesia’s digital culture. Methods: This study used an integrative literature review of studies published from 2005 to 2026, analyzed through Judith Butler’s performativity framework and Consumer Culture Theory (CCT). Of the 187 records initially identified, 38 articles met the inclusion criteria and were analyzed. Results: This study identifies three main findings. First, engineered authenticity has become the dominant IMC strategy, in which marketing effectiveness depends on brands acting as story catalysts rather than narrative centers. Second, UGC practices represent active identity performativity; Indonesian consumers perform their identities by citing social norms related to class, gender, and success, with local characteristics such as identity dualism among nonconventional groups and the negotiation of women’s independence with religious values. Third, consumer content is ambivalent, as it reproduces consumerist ideologies while opening limited spaces for resistance, including parody, criticism, and alternative gender expression, although such resistance tends to be recuperated by platform logic. Conclusion: This study contributes to the integration of IMC as a discursive practice and offers implications for practitioners, particularly regarding transparency in engineered authenticity, and for regulators, especially in developing guidelines for sponsored content labeling.